Treatment delay significantly increases mortality in colorectal cancer: a meta-analysis - Ungvari, Zoltan; Fekete, Mónika; Fekete, János Tibor; Lehoczki, Andrea; Buda, Annamaria; Munkácsy, Gyöngyi; Varga, Péter; Ungvari, Anna; Győrffy, Balázs (GeroScience, 2025)
Delaying the initiation of cancer treatment increases the risk of mortality, particularly in colorectal cancer (CRC), which is among the most common and deadliest malignancies. This study aims to explore the impact of treatment delays on mortality in CRC. A systematic literature search was conducted in PubMed, Web of Science, and Scopus for studies published between 2000 and 2025. Meta-analyses were performed using random-effects models with inverse variance method to calculate hazard ratios (HRs) for both overall and cancer-specific survival at 4-, 8-, and 12-week treatment delay intervals, with heterogeneity assessed through I 2 -statistics and publication bias evaluated using funnel plots and Egger’s test. A total of 20 relevant studies were included in the meta-analysis. The analyses of all patients demonstrated a progressively increasing risk of 12–39% with longer treatment delays (4 weeks, HR = 1.12; 95% CI, 1.08–1.16; 8 weeks, HR = 1.24; 95% CI, 1.16–1.34; 12 weeks, HR = 1.39; 95% CI, 1.25–1.55). In particular, incrementally higher hazard ratios were observed for all–cause mortality at 4 weeks (HR = 1.14; 95% CI, 1.09–1.18), 8 weeks (HR = 1.29; 95% CI, 1.20–1.39), and 12 weeks (HR = 1.47; 95% CI, 1.31–1.64). In contrast, cancer-specific survival analysis showed a similar trend but did not reach statistical significance (4 weeks, HR = 1.07; 95% CI, 0.98–1.18; 8 weeks, HR = 1.15; 95% CI, 0.95–1.39; 12 weeks, HR = 1.23; 95% CI, 0.93–1.63). Treatment delays in colorectal cancer patients were associated with progressively worsening overall survival, with each 4-week delay increment leading to a substantially higher mortality risk. This study suggests that timely treatment initiation should be prioritized in clinical practice, as these efforts can lead to substantial improvements in survival rates.